Advancing and scaling up sexual and reproductive health services for climate adaptation and resilience in Uganda - Nakuya Kasekende, Niona; Kabiswa, Charles; Zake, Joshua; Kansiime, Monica K. (Frontiers in Global Women's Health, 2025)
BackgroundClimate change significantly affects Uganda's economy and human well-being, with disproportionate impacts on the sexual and reproductive health (SRH) services of women and girls. However, SRH remains largely absent from climate change policy frameworks. This study examines the extent to which SRH is integrated into Uganda's climate policy frameworks and explores stakeholder perceptions of the impacts of climate change on SRH to provide insights for more inclusive and integrated policies.MethodsThe study used a mixed-methods approach, combining policy document analysis with primary qualitative data. Key documents reviewed included climate change and health policies, strategies, plans, and national medium- and long-term development frameworks. Forty purposively selected key informants and 24 focus group discussions with 321 participants in Buikwe District were conducted. Qualitative data were analyzed using content analysis to identify key themes and gaps.ResultsUganda's climate policy frameworks acknowledge the gender-differentiated impacts of climate change and highlight the importance of SRH services but fall short of outlining concrete actions to address SRH within climate adaptation and mitigation strategies. Key informants highlighted limited stakeholder awareness and weak institutional coordination as major barriers to integrating SRH into climate action. Community respondents noted that climate extremes degrade critical infrastructure, disrupt access to SRH services and increase vulnerabilities, including a heightened risk of gender-based violence.ConclusionsThe impact of the climate crisis on SRH is increasingly evident, particularly for women and girls, yet Uganda's key climate policies still exhibit lack of concrete actions to address SRH vulnerabilities. Prioritizing SRH within climate adaptation efforts, especially through resilient health systems and livelihood support such as climate resilient agricultural training and vocational programs for women and girls is key to advancing both gender and health equity, and climate resilience in Uganda. This should be supported by robust gender disaggregated data, stronger institutional coordination, and inclusive, community-led planning.